ADDITION OF DEXMEDETOMIDINETO LIGNOCAINE FOR INTRAVENOUS REGIONAL ANESTHESIA IN UPPER EXTREMITY ORTHOPAEDIC SURGERIES - SINGH, SANTOSH KUMAR; MITTAL, GAURAV; ROUT, ASHOK; GAJBHIYE, DEWENDRAJ; KEDAR, PRADEEP (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The objective of this study was to determine the duration of onset and regression time of sensory and motor blocks, the quality of anesthesia, and post-operative analgesia by the addition of dexmedetomidine to local anesthetic solution in intravenous regional anesthesia (IVRA) in upper extremity orthopedic surgeries. Methods: This is a prospective, randomized, and double blind clinical trial. Ninety American Society of Anaesthesiologists Grade I and II patients of either gender between 18 and 60 years of age scheduled for elective upper extremity orthopedic surgeries lasting for <90 min were included in the study. Patients were randomly allocated to two Groups A and B of 45 each. Group A received 3 mg/kg preservative free lignocaine alone and Group B received 3 mg/kg preservative free lignocaine with dexmedetomidine, 0.5 μg/kg in IVRA. Result: Onset time of sensory blockade in Group A and B was 5.6±0.93 min and 3.9±0.63 min, respectively. Onset time of motor blockade in Group A and Group B was 15.01±4.53 min and 10.74±3.64 min, respectively. The difference in onset time of sensory and motor blockade between the two groups was statistically significant (p<0.05). Sensory blockade recovery time after release of tourniquet was 6.9±0.53 min in Group A and 29.21±5.23 min in Group B. Motor blockade recovery time was 4.35±0.76 min for Group A and 12.32±7.23 min for Group B. The difference in sensory and motor blockade recovery time between the two groups was statistically significant (p<0.05). Conclusion: Dexmedetomidine on addition to lignocaine for IVRA provided rapid onset of sensory and motor blockade, prolonged duration of sensory and motor blockade, and reduced tourniquet pain.